Protein S is protective in pulmonary fibrosis. (22nd June 2016) - Urawa, M.; Kobayashi, T.; D'Alessandro‐Gabazza, C. N.; Fujimoto, H.; Toda, M.; Roeen, Z.; Hinneh, J. A.; Yasuma, T.; Takei, Y.; Taguchi, O.; Gabazza, E. C.
Abstract : Essentials Epithelial cell apoptosis is critical in the pathogenesis of idiopathic pulmonary fibrosis. Protein S, a circulating anticoagulant, inhibited apoptosis of lung epithelial cells. Overexpression of protein S in lung cells reduced bleomycin‐induced pulmonary fibrosis. Intranasal therapy with exogenous protein S ameliorated bleomycin‐induced pulmonary fibrosis. Summary: Background: Pulmonary fibrosis is the terminal stage of interstitial lung diseases, some of them being incurable and of unknown etiology. Apoptosis plays a critical role in lung fibrogenesis. Protein S is a plasma anticoagulant with potent antiapoptotic activity. The role of protein S in pulmonary fibrosis is unknown. Objectives: To evaluate the clinical relevance of protein S and its protective role in pulmonary fibrosis. Methods and Results: The circulating level of protein S was measured in patients with pulmonary fibrosis and controls by the use of enzyme immunoassays. Pulmonary fibrosis was induced with bleomycin in transgenic mice overexpressing human protein S and wild‐type mice, and exogenous protein S or vehicle was administered to wild‐type mice; fibrosis was then compared in both models. Patients with pulmonary fibrosis had reduced circulating levels of protein S as compared with controls. Inflammatory changes, the levels of profibrotic cytokines, fibrosis score, hydroxyproline content in the lungs and oxygen desaturation were significantly reduced in protein S‐transgenic mice as compared with wild‐type mice. Wild‐type mice treated with exogenous protein S showed significant decreases in the levels of inflammatory and profibrotic markers and fibrosis in the lungs as compared with untreated control mice. After bleomycin infusion, mice overexpressing human protein S showed significantly low caspase‐3 activity, enhanced expression of antiapoptotic molecules and enhanced Akt and Axl kinase phosphorylation as compared with wild‐type counterparts. Protein S also inhibited apoptosis of alveolar epithelial cells in vitro . Conclusions: These observations suggest clinical relevance and a protective role of protein S in pulmonary fibrosis.